2018
DOI: 10.1158/1078-0432.ccr-17-3783
|View full text |Cite
|
Sign up to set email alerts
|

Radiomics Signature on Magnetic Resonance Imaging: Association with Disease-Free Survival in Patients with Invasive Breast Cancer

Abstract: To develop a radiomics signature based on preoperative MRI to estimate disease-free survival (DFS) in patients with invasive breast cancer and to establish a radiomics nomogram that incorporates the radiomics signature and MRI and clinicopathological findings. We identified 294 patients with invasive breast cancer who underwent preoperative MRI. Patients were randomly divided into training ( = 194) and validation ( = 100) sets. A radiomics signature (Rad-score) was generated using an elastic net in the trainin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
136
1
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 198 publications
(147 citation statements)
references
References 36 publications
9
136
1
1
Order By: Relevance
“…Many studies have confirmed that radiomics has a high clinical application value [16][17][18]. Compared to the histopathological method, radiomics can be used as a "virtual biopsy" technique, can quantitatively analyze the entire tumor tissue, and has no sampling location limitation, thus providing richer and more complete tumor information for clinical diagnosis, treatment, and prognostic evaluation [19][20][21][22]. The applications of radiomics in the field of lung cancer have been investigated widely, and many studies have confirmed its good prospect [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have confirmed that radiomics has a high clinical application value [16][17][18]. Compared to the histopathological method, radiomics can be used as a "virtual biopsy" technique, can quantitatively analyze the entire tumor tissue, and has no sampling location limitation, thus providing richer and more complete tumor information for clinical diagnosis, treatment, and prognostic evaluation [19][20][21][22]. The applications of radiomics in the field of lung cancer have been investigated widely, and many studies have confirmed its good prospect [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Early work utilized parameters calculated from gray level co‐occurrence matrices to discriminate between benign and malignant lesions . Subsequent studies have incorporated more complex measures of image texture to both aid diagnosis and to explore the efficacy of texture analysis in prognosis …”
mentioning
confidence: 99%
“…12 Subsequent studies have incorporated more complex measures of image texture to both aid diagnosis 13 and to explore the efficacy of texture analysis in prognosis. [14][15][16] The pool of literature that specifically focuses on the characterization of small breast lesions utilizing MRI remains limited. Early work assessed morphologic and kinetic characteristics in a cohort of 43 patients with sub-1 cm lesions.…”
mentioning
confidence: 99%
“…A radiomics signature-based nomogram has been developed and validated for preoperative prediction of survival in breast cancer, gastric cancer, and early-stage non-small cell lung cancer patients [28][29][30]. In our study, the developed nomogram incorporated a radiomics score derived from two components of the PET-based features, pN and LVI.…”
Section: Discussionmentioning
confidence: 99%
“…First, various computer algorithms have been used for feature extraction, and the types of features extracted by each algorithm were not uniform. Moreover, we applied standardization of features as a preprocessing step before entering the data into the LASSO COX model, following a method that has already been adopted for radiomics analysis in patients with breast or gastric cancer [28,30]. However, most previous studies of PETderived radiomics analysis in patients with CRC did not use standardization as a preprocessing step [17][18][19]43].…”
Section: Discussionmentioning
confidence: 99%